Forecasting of gross domestic product in Poland and its regional components - Batóg, Barbara (Prognozowanie zmiennej agregatowej oraz jej składowych na przykładzie produktu krajowego brutto, 2011)
The paper presents the forecasts for gross domestic product in Poland and its regional components. The forecasts were set down on the basis of the following models: trends, exponential smoothing and panel data models with an object varying constant. In panel data model there was one exogenous variable – employment in the national economy. The data for employment in a given year are known earlier than data for regional GDP in the same year. Therefore the real values of employment could have been used in calculating the forecasts of GDP. All applied models were well fitted but the forecasts calculated on the base of the panel data model had the smallest relative errors.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 39-47
Keywords: prognozowanie; produkt krajowy brutto (pkb); modele panelowe; forecasting; gross domestic product (gdp); panel model